Renoprotective Effects of Maslinic Acid on Experimental Renal Fibrosis in Unilateral Ureteral Obstruction Model via Targeting MyD88 - Wenjuan Sun; Chang Hyun Byon; Dong Hyun Kim; Hoon In Choi; Jung Sun Park; Soo Yeon Joo; In Jin Kim; Inae Jung; Eun Hui Bae; Seong Kwon Ma; Soo Wan Kim (Frontiers Media S.A., 2021)
Maslinic acid (MA), also named crategolic acid, is a pentacyclic triterpene extracted from fruits and vegetables. Although various beneficial pharmacological effects of MA have been revealed, its effect on renal fibrosis remains unclear. This study was designed to clarify whether MA could attenuate renal fibrosis and determine the putative underlying molecular mechanisms. We demonstrated that MA-treated mice with unilateral ureteral obstruction (UUO) developed a histological injury of low severity and exhibited downregulated expression of fibrotic markers, including α-smooth muscle actin (α-SMA), vimentin, and fibronectin by 38, 44 and 40%, and upregulated expression of E-cadherin by 70% as compared with untreated UUO mice. Moreover, MA treatment restored the expression levels of α-SMA, connective tissue growth factor, and vimentin to 10, 7.8 and 38% of those induced by transforming growth factor (TGF)-β in NRK49F cells. MA decreased expression of Smad2/3 phosphorylation and Smad4 in UUO kidneys and TGF-β treated NRK49F cells (p < 0.05, respectively). Notably, MA specifically interferes with MyD88, an adaptor protein, thereby mitigating Smad4 nuclear expression (p < 0.01 compared to TGF-β treated group) and ameliorating renal fibrotic changes (p < 0.01 for each fibrotic markers compared to TGF-β induced cells). In addition, in the UUO model and lipopolysaccharide-induced NRK49F cells, MA treatment decreased the expression of IL-1β, TGF-α and MCP-1, ICAM-1, associated with the suppression of NF-κB signaling. These findings suggest that MA is a potential agent that can reduce renal interstitial fibrosis, to some extent, via targeting TGF-β/Smad and MyD88 signaling.